Proceedings of the Third Conference on Machine Translation: Research Papers 2018
DOI: 10.18653/v1/w18-6320
|View full text |Cite
|
Sign up to set email alerts
|

Exploring gap filling as a cheaper alternative to reading comprehension questionnaires when evaluating machine translation for gisting

Abstract: A popular application of machine translation (MT) is gisting: MT is consumed as is to make sense of text in a foreign language. Evaluation of the usefulness of MT for gisting is surprisingly uncommon. The classical method uses reading comprehension questionnaires (RCQ), in which informants are asked to answer professionally-written questions in their language about a foreign text that has been machine-translated into their language. Recently, gap-filling (GF), a form of cloze testing, has been proposed as a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…Evidently, the machine-translated subtitles were successful in conveying some of the presented information to the participants. The findings of the quantitative analysis are consistent with those of Forcada et al (2018), who reported a lack of any significant differences in reading comprehension between participants who were provided with different MT outputs and those who were provided with human translations. The researchers stated that this result is a clear indication of the usefulness of raw MT output in assimilating the gist of the presented information.…”
Section: Quantitative Analysissupporting
confidence: 85%
“…Evidently, the machine-translated subtitles were successful in conveying some of the presented information to the participants. The findings of the quantitative analysis are consistent with those of Forcada et al (2018), who reported a lack of any significant differences in reading comprehension between participants who were provided with different MT outputs and those who were provided with human translations. The researchers stated that this result is a clear indication of the usefulness of raw MT output in assimilating the gist of the presented information.…”
Section: Quantitative Analysissupporting
confidence: 85%
“…As alternatives to adequacy and fluency, presented reading comprehension for MT quality evaluation. Forcada et al (2018) proposed gap-filling, where certain words are removed from reference translations and readers are asked to fill the gaps left using the machine-translated text as a hint. Popović (2020) proposed to ask annotators to just label problematic parts of the translations instead of assigning a score.…”
Section: Related Workmentioning
confidence: 99%
“…La métrique TER (Translation EDIT Rate) de Snover et al [2006] illustre cette démarche et permet d'approximer une mesure du temps de post-édition. Avec les progrès des outils de traitement des langues, la mesure automatique d'autres tâches, en particulier de tâches de compréhension, semble envisageable [Scarton and Specia, 2016, Forcada et al, 2018, Krubi ński et al, 2021.…”
Section: 'Evaluer Sans Référenceunclassified